2016
DOI: 10.1038/ismej.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between growth-dependent changes in cell size, nutrient supply and cellular elemental stoichiometry of marine Synechococcus

Abstract: The factors that control elemental ratios within phytoplankton, like carbon:nitrogen:phosphorus (C:N:P), are key to biogeochemical cycles. Previous studies have identified relationships between nutrientlimited growth and elemental ratios in large eukaryotes, but little is known about these interactions in small marine phytoplankton like the globally important Cyanobacteria. To improve our understanding of these interactions in picophytoplankton, we asked how cellular elemental stoichiometry varies as a functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
99
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 58 publications
10
99
1
Order By: Relevance
“…Such a change in cell size means that you cannot simply extrapolate from an increase or a decrease in an individual cell quota (like Q P ) to the stoichiometric ratio. Thus, our study adds to an emerging concept, whereby changes in cell size due to physiological responses to different environmental conditions are important for regulating the elemental composition and ratios in marine Cyanobacteria [16]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a change in cell size means that you cannot simply extrapolate from an increase or a decrease in an individual cell quota (like Q P ) to the stoichiometric ratio. Thus, our study adds to an emerging concept, whereby changes in cell size due to physiological responses to different environmental conditions are important for regulating the elemental composition and ratios in marine Cyanobacteria [16]. …”
Section: Discussionmentioning
confidence: 99%
“…The main suggested controls include nutrient availability, growth rate, temperature, and life history. Extensive experimental and model studies have demonstrated a strong effect of nutrient availability, whereby a low supply of nitrogen or phosphorus leads to a low cell quota ( Q ) of the corresponding element [13ā€“16]. Another important factor is the cellular allocation towards P rich ribosomes at elevated growth rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patterns can be categorized into 3 broad classes: (1) both N:C and P:C increasing with dilution rate under N-and P-limitation (B. pendula, ƅgren, 2004); (2) only the limiting nutrient correlates with dilution rate (Scenedesmus sp., Rhee, 1974); (3) the asymmetric response, i.e., N:C increasing with dilution rate both at N-and P-limitation, but P:C increases only when P is limiting, (S. linearis and S. minutum, Elrifi and Turpin, 1985;Healey, 1985). Also using a Synechococcus strain, however in a constrained range of growth rates, Garcia et al (2016) found similar asymmetric patterns. Those patterns were previously addressed by alternative model approaches (e.g., ƅgren, 2004;Flynn, 2008;Bougaran et al, 2010;Bonachela et al, 2013;Pahlow et al, 2013).…”
Section: Discussionmentioning
confidence: 58%
“…Some of the difference may have to do with cooccurring mutations, e.g., cardiolipin synthetase (cls) association with rho or rod-shape genes, which affect cell shape, and their association with rpoB (Tenaillon et al, 2012). Size of the cell may directly impact the cell stoichiometry, as seen in marine bacteria (Garcia et al, 2016). These affiliated mutations may be affecting the composition of cell membranes, for example, resulting in differential C:N:P.…”
Section: Discussionmentioning
confidence: 99%